Representation, News Media and the Institute of Education and Research at the University of Dhaka (Teacher’s World: Journal of Education and Research, 2023)
Looking into representation in news media is a kaleidoscopic yet momentous way to learn how an institution such as the Institute of Education and Research (IER), University of Dhaka, is portrayed and viewed by many. News being just a fingertip away today and somewhat invasive, representation in the news has become more meaningful, far-reaching, and policy-influencing. This content analysis research searched five Bangladeshi news media, both newspapers and broadcast media, over a five-year period, from 2016 to 2020, to understand the nature of IER’s representation in them. The findings reveal that IER is primarily considered an authoritative institution in the field of education and research in Bangladesh, with secondary representation in assorted feature stories. IER faculty members were consulted for their insights into various education and concomitant topics. IER students were also represented, although relatively less significantly, in the form of success stories and soft news articles. A smaller amount of unpropitious representation of IER was also found.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.109-129